Empty Chair sebagai Media Ekspresi Emosi: Studi Literatur dalam Konteks Terapi Gestalt - Safitri, Adhwa Kayla; Nurizza, Najma Aghnia; Khairat, Imalatul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The inability to express emotions in a healthy manner can lead to serious psychological consequences, especially for students facing social pressure, academic stress, or interpersonal conflicts. This article aims to examine the Empty Chair technique in Gestalt therapy as a medium for emotional expression through a literature study approach. The research was conducted using a qualitative method by reviewing relevant scholarly sources from the last 10–15 years. The findings indicate that the Empty Chair technique provides a safe space for individuals to express repressed emotions, resolve internal conflicts, and build self-awareness through imaginative dialogue. This technique has been proven effective in various contexts, such as reducing anxiety symptoms, addressing inner child wounds, improving self-esteem, and decreasing withdrawal behavior in bullying victims. Therefore, Empty Chair holds significant potential to be implemented in school guidance and counseling services as a strategic alternative to support students’ emotional well-being.